Revitalizing Character Education in The Digital Age Based on The Principle of "Ing Ngarsa Sung Tuladha" by Ki Hajar Dewantara - Dita Puspita Dewi; Gita Putri Ramadhani; Zahra Aulia Hanifa; Sofyan Sauri (PAEDAGOGIA, 2025)
This study examines the revitalization of character education in Indonesia by recontextualizing Ki Hajar Dewantara’s principle “Ing Ngarsa Sung Tuladha” (to lead by example) within the dynamics of the digital age. Utilizing a qualitative literature review, the research identifies three core challenges hindering effective moral education: the erosion of professional teacher identity due to administrative overload, increasing ethical breaches in digital interactions, and fragmented policy implementation that fails to support value-based learning. The study finds that restoring teachers’ moral leadership is essential for embedding ethical behavior in educational settings, both offline and online. To address these issues, an integrative character education framework is proposed, combining the Among pedagogical approach, the Tripusat Pendidikan system (family, school, and community synergy), and the 4N model (Niteni, Nirokke, Nambahi, Nularke) for value internalization. This model fosters the embodiment of ethical values through consistent teacher role-modeling, community involvement, and culturally grounded pedagogy. The study concludes that character education in the digital era demands a systemic transformation, restoring the teacher’s role as a moral exemplar, aligning educational practices with local wisdom, and reinforcing ethical technology to cultivate morally resilient students equipped to navigate contemporary challenges